2012
DOI: 10.1007/s00526-011-0485-9
|View full text |Cite
|
Sign up to set email alerts
|

The optimal mass transport problem for relativistic costs

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 29 publications
2
42
0
Order By: Relevance
“…The conditions are met on a weakly dense subset of pairs of measures by Corollary 2.9. Theorem 2.8 generalizes results in [6,7,17]. The condition of strict timelikeness is related to parts of the definition of q-separated measures in [17].…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…The conditions are met on a weakly dense subset of pairs of measures by Corollary 2.9. Theorem 2.8 generalizes results in [6,7,17]. The condition of strict timelikeness is related to parts of the definition of q-separated measures in [17].…”
Section: Introductionsupporting
confidence: 61%
“…The theorem generalizes [6,Theorem 5.13] and [7,Theorem B]. Note that Theorem 2.8 is most likely optimal, as Theorem 2.12 shows that dual solutions cannot exist whenever there are optimal couplings transporting a set of positive measure along ∂C, the boundary of the lightcone.…”
Section: Proposition 23 ([21]mentioning
confidence: 80%
“…In this paper, we consider the classical mass transport problem with a particular class of cost functions c. While the case when c is strictly convex and real-valued is well understood (we refer to [34] for a survey), our goal is to continue the study of a wide class of non real-valued cost functions, called "relativistic costs", which were introduced in [12] as a generalization to the "relativistic heat cost".…”
Section: Introductionmentioning
confidence: 99%
“…Afterwards, the corresponding relativistic heat equation has also been studied by McCann and Puel in [28] by means of the Jordan-Kinderlehrer-Otto approach introduced in [25], and by Andreu, Caselles and Mazón via PDE methods in a series of papers [3,5,4,6,7,8,9,16]. We refer to [14,12] and the references therein for more on this topic. Notice that, from the mathematical point of view, a quite interesting feature of this cost function is that it is strictly convex and bounded on its domain, hence in particular it is not continuous on R n × R n (while the non real-valued cost functions have been often considered as continuous, see for instance [23,22,29,30,33,11]).…”
Section: Introductionmentioning
confidence: 99%
“…The latter is a new and fast-developing area of research [10,13,55], 1 which has found successful applications in the early universe reconstruction problem [14,[28][29][30].…”
Section: Introductionmentioning
confidence: 99%